Comments on the cross-relaxation effect between adsorbed ³He and PrF₃ nanoparticles - Alakshin, E.M.; Gazizulin, R.R.; Gazizulina, A.M.; Klochkov, A.V.; Orlinskii, S.B.; Rodionov, A.A.; Safin, T.R.; Safiullin, K.R.; Tagirov, M.S.; Zakharov, M.Yu. (Физика низких температур, 2015)
The spin kinetics data of ³He in contact with PrF₃ and LaF₃ nanosized powders are reported. All experiments have been carried out by pulse NMR methods at temperature 1.5 K. The analysis of obtained data testifies in favor of cross-relaxation presence in the nuclear spin–lattice relaxation data, which takes place between ³He and ¹⁴¹Pr nuclei.